INITIAL STUDIES OF THE MARINE GEOPHYSICAL SURVEY IN THE OFFSHORE WAIGEO, WEST PAPUA - Dida Kusnida; Subarsyah Subarsyah; Eko Saputro; arif ali (Jurnal Geologi dan Sumberdaya Mineral, 2016)
The offshore northern Waigeo situated and evolved within the obliquely converging of the Australian and Pacific plates boundary zone and Â bound by an active left-lateral transform fault of the Sorong Fault Zone (SFZ) in the southern part. In general the Waigeo waters characterized by +200 nT to -150 nT of total magnetic intensities which indicate that the study area possibly overlain by a homogenous rock of oceanic origin in the form of highs (terranes) and lows (basins).Â  Seismic data indicate that the morphology of the study area relatively steep due to the tectonic contact boundary between island-terranes of Waigeo and between Ayu islands and Pacific Oceanic crust. This tectonic contact boundaries characterized by the present of Waigeo Trough that extends southeast-northwest direction. Seismic data reveal about 1000 meters thick of acoustically chaotic to laminated, indicate fine-grained sediments of slumps at Waigeo Trough slope and trough floor, and about 1500 meters thick of pelagic sediments at the Ayu Trough.